ESSENCE OF PANCHAKARMA IN THE MANAGEMENT OF SHIRO ROGA (International Journal of Food and Nutritional Sciences, 2021)
In Ayurveda, the treatment protocols of Panchakarmas includes Vamana, Virechana, Nasya, Basthi, and Raktamokshana, according to Acharya Susrutha. To remove the morbid Doshas from the body, these are recommended in various illness types. Shiras, the seat of Prana and Indriyas, is regarded as the Uttamanga of the body. It's one of the three principal Marmas. The head is home to all three doshas, with Kapha dosha predominating. Eleven varieties of Shiro Roga have been mentioned by Acharya Sushrutha. One of the top five clinical illnesses in the world, according to the WHO, is headache. Over 46% of people worldwide suffer from headaches, and over 90% of people will experience one at some point in their lives. Increased headache frequency is mostly linked to increased family, social, and financial stress. The three primary drug classes used to treat headache disorders are analgesics, anti-emetics, and targeted anti-migraine medicines. Ayurveda's panchakarma is an essential component. The Nasya is regarded as the most effective and specialized technique for Shiro Roga among these. However, further Panchakarma therapies are also crucial in the management of Shiro Rogas. An analysis of the Panchakarma therapies mentioned in Shiro Roga and mentioned by Acharya Susrutha in Susrutha Samhitha Uttara Tantra is attempted here.